ALGUNAS APLICACIONES RECIENTES DE LA TÉCNICA DE RADIO OCULTAMIENTO SATELITAL EN EL ESTUDIO DE PROCESOS ATMOSFÉRICOS - Alejandro de la Torre; Pedro Alexander; Pablo Llamedo; Rodrigo Hierro; Horacio Pessano; Andrés Odiard (Boletín Geográfico)
In the last years, the use of radio occultation (RO) technique to observe the terrestrial atmosphere and the climate takes advantage of the occultation of the Sun, the Moon, the stars and principally of artificial satellites of low height (LEO). In the latter case, crossed signs between LEO and GPS satellites are used. The application of RO's technology using transmitters of the GPS system in high orbits and recipients on board of low orbit satellites, has provided profiles of atmospheric refractivity very precise. The basic idea of a RO is to observe how waves emitted by a GPS are propagated in the atmosphere. The ray trajectory associated to a radio wave between a GPS and a LEO, while these are hiding themselves mutually due to the interposition of the Earth, is deviated due to refractivity gradients. The ray bending angle is obtained from a change in the phase (Doppler shift) of the signal received by the LEO. Assuming spherical symmetry, the deviation information may be inverted by an Abel transformation to obtain a vertical profile of the index of refraction. From atmospheric profiles of refractivity and an atmospheric model, several parameters are obtained: from temperature (T), pressure, geopotential height and water vapor to minor species as aerosols, cloud liquid water and ionospheric electron density. The enormous advantage offered by the coverage in the whole planet, above the continental and oceanic territories, the 1K T resolution, the long term stability and mainly the absence of any restriction imposed by climatic conditions, makes the GPS RO technique unique among different remote sensing atmospheric systems. Up to now, hundreds of thousands of soundings have been processed, from the first satellites to recent (SAC-C, CHAMP, GRACE, COSMIC, TerraSAR-X, MetOp). In the present work, examples of global and regional water vapor and atmospheric wave energy distributions will be shown. It will be put on special emphasis on the mountainous regions of the Andes Range at middle latitudes and the Antarctic Peninsula and case studies will be analyzed. This analysis will be complemented by WRF model simulations and with measured T profiles in the regions of interest. In particular it will be shown: i) the spatial distribution of stationary gravity waves, ii) their propagation in the lower and middle atmospheres, and iii) the possible relevance of mountain waves as a triggering mechanism of seep convection processes with hail production. Key words: satellite radio occultation, gravity waves.